CALCULATION ESTIMATION OF OVERVOLTAGE ON INSULATION OF THE EQUIPMENT OF A SUBSTATION AT THE LIGHTNING STRIKE IN ITS LIGHTNING ARRESTER - I. V. Nizhevskyi (National Technical University "Kharkiv Polytechnic Institute", 2019)
Purpose. The complex approach to calculating thunderstorm overvoltage on substation equipment is considered when lightning strikes in a lightning rod. Methodology. The conditions of safe passage of lightning current through a lightning arrester are formulated. Results. It is shown that the calculation of the permissible length of air insulating gaps in the substation is based on the breakdown of the air tension, which is assumed to be 500 kV/m. This leads to an error in calculating the length of the air gap and, as a consequence, the probability of its breakdown, the value of which is used to calculate the indicator of the lightning resistance of the substation. A technique is proposed for calculating the permissible voltage on the transformer case when a lightning strike strikes the lightning receptacle of the transformer portal. On the basis of the nonlinear pulsed electric strength of the ground, the specified minimum permissible ground distance between the grounding rod of the lightning rod and the nearest point of the protected device is obtained. Originality. Refined calculation of the length of the minimum breakdown gap in the air and in the ground. Practical value. The proposed approach makes it possible to calculate thunderstorm overvoltage on substation equipment.